Mitochondrial diversity and the origins of African and European cattle. - Bradley, D G (1996)
The nature of domestic cattle origins in Africa are unclear as archaeological data are relatively sparse. The earliest domesticates were humpless, or Bos taurus, in morphology and may have shared a common origin with the ancestors of European cattle in the Near East. Alternatively, local strains of the wild ox, the aurochs, may have been adopted by peoples in either continent either before or after cultural influence from the Levant. This study examines mitochondrial DNA displacement loop sequence variation in 90 extant bovines drawn from Africa, Europe, and India. Phylogeny estimation and analysis of molecular variance verify that sequences cluster significantly into continental groups. The Indian Bos indicus samples are most markedly distinct from the others, which is indicative of a B. taurus nature for both European and African ancestors. When a calibration of sequence divergence is performed using comparisons with bison sequences and an estimate of 1 Myr since the Bison/Bos Leptobos common ancestor, estimates of 117-275,000 B.P. and 22-26,000 B.P. are obtained for the separation between Indians and others and between African and European ancestors, respectively. As cattle domestication is thought to have occurred approximately 10,000 B.P., these estimates suggest the domestication of genetically discrete aurochsen strains as the origins of each continental population. Additionally, patterns of variation that are indicative of population expansions (probably associated with the domestication process) are discernible in Africa and Europe. Notably, the genetic signatures of these expansions are clearly younger than the corresponding signature of African/European divergence.